The Impact of Rainfall on Fecal Coliform Bacteria in Bayou Dorcheat (North Louisiana) - Hill, Dagne D. (Molecular Diversity Preservation International (MDPI), 2006)
Fecal coliform bacteria are the most common pollutant in rivers and streams. In Louisiana, it has been reported that 37% of surveyed river miles, 31% of lakes, and 23% of estuarine water had some level of contamination. The objective of this research was to assess the effect of surface runoff amounts and rainfall amount parameters on fecal coliform bacterial densities in Bayou Dorcheat in Louisiana. Bayou Dorcheat has been designated by the Louisiana Department of Environmental Quality as a waterway that has uses such as primary contact recreation, secondary contact recreation, propagation of fish and wildlife, agriculture and as being an outstanding natural resource water. Samples from Bayou Dorcheat were collected monthly and analyzed for the presence of fecal coliforms. Fecal coliforms isolated from these samples were identified to the species level. The analysis of the bacterial levels was performed following standard test protocols as described in Standard Methods for the Examination of Water and Wastewater. Information regarding the rainfall amounts and surface runoff amounts for the selected years was retrieved from the Louisiana Office of State Climatology. It was found that a significant increase in the fecal coliform numbers may be associated with average rainfall amounts. Possible sources of elevated coliform counts could include sewage discharges from municipal treatment plants and septic tanks, storm water overflows, and runoff from pastures and range lands. It can be concluded that non-point source pollution that is carried by surface runoff has a significant effect on bacterial levels in water resources.